2013
DOI: 10.1016/j.virol.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Autographa californica M nucleopolyhedrovirus open reading frame 109 affects infectious budded virus production and nucleocapsid envelopment in the nucleus of cells

Abstract: Autographa californica M nucleopolyhedrovirus (AcMNPV) open reading frame 109 (ac109) is conserved in all known baculovirus genomes, suggesting a crucial role in virus replication. Although viruses lacking ac109 have been previously characterized, the phenotypes differ from production of non-infectious virions to lack of virion production. To re-examine ac109 function, we constructed a recombinant AcMNPV bacmid, AcBAC109KO, with a deletion in ac109. We did not detect infectious budded virus after transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Therefore, our results suggest that AC78 executes its function after nucleocapsid assembly, during nucleocapsid envelopment and ODV embedding. Previous studies have reported that OBs without embedded virions can be formed in cells transfected with knockout viruses, ac98 (38K) (58), ac142 (59), ac103 (p48) (60), ac53 (61), ac76 (62), ac94 (39), and ac109 (63,64). Deletion of ac98 (38K) or ac53 leads to defects in nucleocapsid assembly, whereas knockout of ac142, ac103 (p48), ac76, or ac109 interferes with nucleocapsid envelopment, which is similar to what we observed for ac78 knockout in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that AC78 executes its function after nucleocapsid assembly, during nucleocapsid envelopment and ODV embedding. Previous studies have reported that OBs without embedded virions can be formed in cells transfected with knockout viruses, ac98 (38K) (58), ac142 (59), ac103 (p48) (60), ac53 (61), ac76 (62), ac94 (39), and ac109 (63,64). Deletion of ac98 (38K) or ac53 leads to defects in nucleocapsid assembly, whereas knockout of ac142, ac103 (p48), ac76, or ac109 interferes with nucleocapsid envelopment, which is similar to what we observed for ac78 knockout in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been some controversy regarding the source of the intranuclear microvesicles, considerable evidence has been generated to support the hypothesis that these microvesicles are the result of budding of the nuclear membrane into the nucleoplasm (6). Several viral genes, including ac11, ac76, ac93, ac94 (odv-e25), ac103 (p48), and ac109, have been reported to be required for ODV envelopment (19)(20)(21)(22)(23)(24)(25). However, little is known regarding the genes that affect the morphogenesis of intranuclear microvesicles.…”
mentioning
confidence: 99%
“…Additional viral envelope proteins E18, ODV-E56, and ODV-E66 are also enriched in intranuclear microvesicles (43,63,64). Deletion of E25, E18, AC76, AC92, and AC109 resulted in either no or reduced ODV production (47,48,(59)(60)(61)(65)(66)(67). These proteins are considered to be involved in envelopment of ODV.…”
Section: Discussionmentioning
confidence: 99%